Femtosecond laser–assisted compared with standard cataract surgery for removal of advanced cataracts. Issue 9 (September 2015) - Hatch, Kathryn M.; Schultz, Tim; Talamo, Jonathan H.; Dick, Burkhard H.
Abstract : Purpose : To compare effective phacoemulsification time (EPT) for the removal of brunescent cataracts treated with femtosecond laser–assisted cataract surgery with standard cataract phacoemulsification techniques. Setting : Ruhr University Eye Hospital, Bochum, Germany. Design : Comparative prospective case study. Methods : The Lens Opacities Classification System III (LOCS III) grading system was used to measure eyes divided into 4 groups having cataract surgery. Groups 1 and 2 contained eyes with LOCS III grade nuclear opalescence (NO) 3 cataracts treated with standard cataract surgery and femtosecond laser–assisted cataract surgery, respectively. Groups 3 and 4 contained brunescent cataracts, LOCS III grades NO5, treated with standard cataract surgery and femtosecond laser–assisted cataract surgery, respectively. Results : There were 240 eyes, with 60 eyes in each group. The EPT in Group 1 ranged from 0.46 to 3.10 (mean 1.38); the EPT in all eyes in Group 2 was 0 ( P < .001). The EPT in Groups 3 and 4 was 2.12 to 19.29 (mean 6.85) and 0 to 6.75 (mean 1.35), respectively ( P < .001). A comparison between EPT in Groups 1 and 4 showed that EPT in Group 4 was also lower than in Group 1 ( P = .013). Groups 4 and 1 were the most statistically similar of all groups compared, suggesting that EPT for a femtosecond laser–treated grade 5 cataract was most similar to that of a standard‐treated grade 3 cataract. Conclusion : Femtosecond laser pretreatment for brunescent cataracts allowed for a significant reduction in EPT compared with manual standard phacoemulsification techniques. Financial Disclosure : Drs. Hatch, Talamo, and Dick are consultants to Abbott Medical Optics, Inc. Dr. Schultz has no financial or proprietary interest in any material or method mentioned.